RESPONS PETANI TERHADAP PROGRAM ASURANSI USAHA TANI PADI (AUTP) DI KECAMATAN ADIMULYO KABUPATEN KEBUMEN - Khasanah, Rumiati; Suwarto, Suwarto; Wijianto, Arip (Universitas Sebelas Maret, 2020)
This research aims to analyze the responses of farmers to the AUTP program; to analyze the factors affecting farmers’ responses to the AUTP program; and to analyze the influence of factors affecting responses to farmers’responses in the AUTP program. This research was conducted in Adimulyo Subdistrict, Kebumen Regency with the consideration of Adimuluyo Subdistrict is one of the regions that has implemented the AUTP program. This research used quantitative methods and survey technique. The sampling technique used was proportional random sampling. The data sources used were primary and secondary data with methods of observation, interviews, documentation and recording. The analysis method used was multiple linear regression. The results showed that the farmers’ responses to the program from the aspects of understanding, acceptance and implementation of the majority of farmers’responses were in the category of highly disagree with the program. Factors that can influence the responses of the majority were in the very low category, such as formal education, non-formal education, personal experience of rice farming, cultivated land area. Only the age factor was middle-aged, income was low, and mass media access was never. There was a significant influence between the independent variables to the dependent variable in the AUTP program. Independent variables that significantly affected were age (X ), non- formal education (X ), income (X ), personal experience of rice farming (X ), cultivated land area (X ) and mass access (X ). Other variable that didn’t significantly affected the responses of farmers in the AUTP program was formal education (X ).